Submission spatial vicissitudes fatal risk ground in mathematical form - Государська, І.Л. (Proceedings of National Aviation University (archive), 2006)
Variability of the grounding fatality risk by mathematically when taken into account of distance measurement to the airport is considered and definition of the variability of the grounding fatality risk by mathematically was represented.